Hepatotoxicity and acute kidney injury associations with itraconazole, voriconazole and posaconazole in the treatment of Onychomycosis: pharmacovigilance study of FDA adverse event reporting system data (FAERS) - Hossain, Ragib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.